Do not confuse multidisciplinary task management in nursing homes with interprofessional care!. Issue 6 (19th June 2017) - Tsakitzidis, Giannoula; Anthierens, Sibyl; Timmermans, Olaf; Truijen, Steven; Meulemans, Herman; Van Royen, Paul
Abstract : Problem statement: Little is known about how interprofessional healthcare providers in nursing homes work together. We know that interprofessional teamwork evolves from trial and error learning and so interprofessional collaboration has to be actively taught. This study aims to gain insights in the perception of professionals towards interprofessional collaboration in nursing homes and the factors that have an impact on interprofessional collaboration. Approach: A qualitative descriptive methodology using focus group interviews and additional semi-structured interviews was performed. In total three focus group sessions with healthcare providers from different disciplines were held and additionally nine semi-structured interviews were executed. A thematic analysis was performed. The transcripts were read to immerse in the data and initial ideas were noted. Both open coding (identification of primary themes) and axial coding (analysis of relationships among themes) were conducted and re-focussed into potential themes. Findings: Four main themes emerge from the analysis: context, collaboration, care and experience. From the findings it seems that healthcare teams in nursing homes work as 'separated groups'. A lot of collaboration is perceived, but no common vision or responsibility sharing is found. The role description of the different disciplines does not always seem clear or is not always explicit. Conclusion: In usual care the perceived interactions between professionals are called collaboration. Obviously physicians and all healthcare professionals do not work interprofessionally according to definitions from the literature. This study provided evidence of the awareness that interprofessional collaboration in usual care is situational and fragmentary organised.